Mit integrativer Innovationspolitik ländliches Potenzial erschließen - Petrik Runst; Jörg Thomä (Wirtschaftsdienst, 2025)
Innovationspolitik begünstigt häufig urbane Regionen. Innovationsgetriebenes Wachstum muss aber nicht den Ballungsräumen vorbehalten sein. Aktuelle Forschungsergebnisse zu jungen innovativen Unternehmen in Deutschland zeigen, dass Innovation in ländlichen Regionen durch alternative Formen gedeihen kann, die sich als "Learning by Doing, Using, Interacting (DUI)" zusammenfassen lassen. Um diese zu fördern, braucht es eine neue, eine integrativere Innovationspolitik. – – Innovation policy often focuses on research and development (R&D) and favours urban centres, therefore rural regions are frequently overlooked. This paper challenges the underlying assumption that innovation-driven growth predominantly occurs in metropolitan areas. Using recent research on young innovative firms in Germany, it demonstrates that innovation in rural areas can flourish through alternative modes of innovation beyond R&D, which can be summarised as 'learning by doing, using and interacting (DUI)'. The findings advocate a broader understanding of innovation that recognises the unique strengths of rural regions. A more inclusive innovation policy could reconcile the goals of economic efficiency and regional equity more effectively than was previously thought possible
Keywords: L26; R11; O38; 330